13C and 119Sn NMR spectra of some monophenyltin(IV) compounds - Pejchal, Vladimír; Holeček, Jaroslav; Lyčka, Antonín (Univerzita Pardubice, 1996)
The 13C and 119Sn NMR spectra of some monophenyltin(IV) compounds in solution of non-coordinating (CDCl3) and coordinating ((CD3)2SO) solvents have been studied. From the values of δ(119Sn), 1J(119Sn, 13C) and additional 13C NMR parameters the coordination numbers of the central tin atom and the shapes of coordination polyhedra around the tin atom have been evaluated.